Critical literature review on concrete crack repairs - Hove, Grandeur Tofara (Department of Civil Engineering, 2019)
This dissertation focuses on an in-depth review of literature on concrete crack repairs. Deterioration of concrete affects both the aesthetics and the integrity of structures. As a result, there is need to repair such defects in order to restore the aesthetics and the integrity of concrete structures. This research discusses concrete crack repairs taking into consideration the mechanisms resulting in concrete cracking, techniques to determine concrete cracking, practices for prevention of concrete cracking and concrete crack repair techniques. Causes of cracking include alkali silica reactions (ASR), steel reinforcement corrosion, shrinkage, thermal variations, foundation movements, soil settlement, vegetation effects and cracking related to earthquale effects. Non-destructive and destructive techniques to determine conrete cracking shall be discussed. Destructive techniques usually involve core drilling of samples whilst non-destructive techniques include visual inspections, ultrasonic pulse velocity test, acoustic emission, spectral analysis of surface waves, modal analysis, petrographic analysis and infrared thermography. Several concrete crack repair techniques are to be discussed such as epoxy injection, routing and sealing, near surface reinforcement, additional reinforcement, gravity filling, grouting, dry packing, crack arrest, polymer impregnation, overlay and surface treatments, crack filling, crack sealing, blanketing, stitching and external stressing. These techniques are applied differently depending on the nature and cause of the concrete cracks. Further discussions will be on various case studies around the world on concrete crack repair which demonstrate the application of various concrete crack repair techniques to different types of concrete cracking scenarios. The case studies also highlight recent developments in technology, repair materials, application fields for various techniques and limitations to concrete crack repair. Some of the case studies discussed include concrete crack repair due to ASR damage on transport infrastructure in USA, ASR effects and crack repairs on a two storey building in California (USA), ASR effects and crack repairs to concrete structures in Hokuriku District in Japan, ASR effects and crack repairs to a gravity dam in India, crack repairs at Buttermarket Shopping Center due to shrinkage cracking and concrete crack repairs in Cheshire due to thermal effects.